-4(u+5)+3u=

Simple and best practice solution for -4(u+5)+3u= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(u+5)+3u= equation:


Simplifying
-4(u + 5) + 3u = 0

Reorder the terms:
-4(5 + u) + 3u = 0
(5 * -4 + u * -4) + 3u = 0
(-20 + -4u) + 3u = 0

Combine like terms: -4u + 3u = -1u
-20 + -1u = 0

Solving
-20 + -1u = 0

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '20' to each side of the equation.
-20 + 20 + -1u = 0 + 20

Combine like terms: -20 + 20 = 0
0 + -1u = 0 + 20
-1u = 0 + 20

Combine like terms: 0 + 20 = 20
-1u = 20

Divide each side by '-1'.
u = -20

Simplifying
u = -20

See similar equations:

| 10d-6=4s-15-3d | | 3(5-4a)=99 | | 6x+5+4x-3=122 | | -92=4(3k-2) | | 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 | | 2(3x-4)=118 | | (4-1/2c)-1/3[3/4(1-2c)]1/12c | | 2x+5=-4x-6 | | (64m^1/2n÷m^-2n4/3)^1/2 | | 203/x=7 | | x/21=21 | | 4x+6=-2x-6 | | 14y^2-12y+3=0 | | e^2x=-4x | | .30x+6y=200 | | 3.5y-2.5y-6.3=-1.0-2.5 | | 2x+3-8(x+1)=3x+2 | | 5q+6=20 |

Equations solver categories